(untitled) (The Pakistan Development Review, 2021)
The study examines the existence of interest rate pass-through between retail interest rates and policy rates in Pakistan using monthly data from January 2004 to March 2017. Both retail interest rates and policy rates follow stylised properties of financial time series. Therefore, the EC-E-GARCH-M model is used to estimate the interest rate pass-through between retail and policy rates as suggested by Wang and Lee (2009). Empirically, there is an incomplete pass-through from policy rates to retail interest rates, which is 73 percent basic points. This rate of pass-through is higher compared to previous studies for Pakistan. The results also highlight that there is an upward rigidity in the deposit rate model. JEL Classifications: C22, C58, Keywords: EC-E-GARCH-M Model, Interest Rate Pass-Through, Stylised Properties, Threshold Asymmetric Cointegration, Rigidities